2018
DOI: 10.14260/jemds/2018/180
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Epidemiological Study of Childhood Vitiligo

Abstract: BACKGROUNDVitiligo is a disorder of melanocytes characterised by depigmentation and is a psychologically devastating disorder. Childhood vitiligo has different epidemiological clinical characteristics that manifests as circumscribed achromic macules often associated with leukotrichia and histologically by degeneration and disappearance of melanocytes in the involved skin and not infrequently in the pigment epithelium of the eyes, leptomeninges and inner ear. Vitiligo can develop at any age and most commonly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Furthermore, it has also been reported also that raised level of glibenclamide was observed in presence of moxifloxacin at different pH levels using UV spectrophotometer. 12 In another study it was reported that moxifloxacin lowered blood glucose level in non-diabetic and diabetic animals and has effect on the hypoglycemic action of oral anti-diabetics in the alloxan diabetic rabbits. [16][17][18][19][20]…”
Section: In Vitro Interaction Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, it has also been reported also that raised level of glibenclamide was observed in presence of moxifloxacin at different pH levels using UV spectrophotometer. 12 In another study it was reported that moxifloxacin lowered blood glucose level in non-diabetic and diabetic animals and has effect on the hypoglycemic action of oral anti-diabetics in the alloxan diabetic rabbits. [16][17][18][19][20]…”
Section: In Vitro Interaction Studiesmentioning
confidence: 97%
“…The risk of dysglycemia increases with concomitant use of oral hypoglycemic agents and oral fluoroquinolones. 12 It is also reported that changes in pharmacokinetics of moxifloxacin occur when it is taken with high calorie or breakfast with high fat contents. Interaction of moxifloxacin is also reported with sucralfate and iron supplement and was evaluated for dysglycemia mostly by clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…Because rainfall occurs based on a specific time and there is a correlation between the previous data and subsequent ones, the best method for analysing rainfall data is using time series [18] revealing that a researcher with data for a past period can use Univariate Box-Jenkins method to forecast values without having to search for other related time series data. Montgomery and Johnson [13] considered the Box and Jenkins methodology the most accurate method for forecasting of time series. [9] in studying of drought, modelling and forecasting the precipitation of the Shiraz city of Iran, used three models; Box-Jenkins, Decomposition and Heat Winterz on precipitation for the period 1977 to 2010 [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the factors includes climate change, topography and orographic effects, atmospheric circulation, vegetation and land use changes, human activities etc [16]. In climate change, the rising global tempratures alter atmospheric circulations patterns, leading to changes in the precipitation patterns [13]. This has been resulting in shifts in rainfall distribution intensity and frequency leading to more frequent droughts or intense rainfall events.…”
Section: Introductionmentioning
confidence: 99%